MANAJEMEN KERJASAMA PEMERINTAH DAN SWASTA DALAM MENGELOLA PENUMPUKAN SAMPAH DI KOTA PEKANBARU - Oktavia, Ria Septi; Harahap, Tuti Khairani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The dynamics development of Pekanbaru that has improved rapidly accompanied by population growth, industry, investment, and the trade that has been developed quickly in Pekanbaru which has brought the consequences to garbage volume improvement by the societies, where as the government officer ability in handling the garbage problems is very limited. This time, Public Service of Pekanbaru has appointed Private Service in handling the garbage problems. There is Multi Inti Guna Ltd. to keep environment clean. Multi Inti Guna Ltd. has duties to monitoring and carrying out the garbage at eight of twelve sub districts in Pekanbaru, meanwhile the other sub districts is managed by Purity and Horticulture Service of Pekanbaru.This research was conducted in Pekanbaru. The objective of this research was analyzed and known the factors that have influenced in implementation of handling the garbage problems that has been done by Purity and Horticulture Service gathered to Multi Inti Guna Ltd. in Pekanbaru. The theory of this research used the theory of George R. Terry about the function of management. Private Partnerships in Managing Stacking Waste management is needed in this accumulation of garbage management activities. Therefore, the authors used management theory.This research is done by using descriptive qualitative method. The technique of sample taken is using Purposive Sampling. The technique of data collection used observation method, interview, and documentation.This research was findings about the management of public private partnership in handling the garbage problems in Pekanbaru. The researcher finds that there is still ineffective and optimum of public private partnership in handling the garbage problems in Pekanbaru. The influence factors in handling the garbage problems in Pekanbaru is population growth, societies’ knowledge and participation, human resources, infrastructures, and funds.Key Words : Management, Public Private Partnership, Piling Garbage